Orange Light-Driven C(sp2)-C(sp3) Cross-Coupling via Spin-Forbidden Ir(III) Metallaphotoredox Catalysis - Xie, Katherine A.; Bednarova, Eva; Joe, Candice L.; Lin, Chenxi; Sherwood, Trevor C.; Simmons, Eric M.; Lainhart, Brendan C.; Rovis, Tomislav (Journal of the American Chemical Society, 2023)
We report the development and characterization of a library of Ir(III) photocatalysts capable of undergoing spin-forbidden excitation (SFE) under orange light irradiation (595 nm). These catalysts were successfully applied to the construction of synthetically valuable C(sp(2))-C(sp(3)) bonds inaccessible with existing methods of low-energy light-driven dual nickel/photoredox catalysis, demonstrating the synthetic utility of this photocatalyst family. The photocatalysts are capable of accessing both oxidatively and reductively activated coupling partners, illustrated through deaminative arylation and potassium alkyl trifluoroborate cross-coupling reactions with aryl halides. We demonstrate diverse substrate scopes of both cross-coupling paradigms under mild conditions in the first example of low-energy light-driven C(sp(2))-C(sp(3)) metallaphotoredox coupling.